Impact of the native-state stability of human lysozyme variants on protein secretion by Pichia pastoris. - Kumita, JR; Johnson, R; Alcocer, M; Dumoulin, M; Holmqvist, F; McCammon, MG; Robinson, C; Archer, D; Dobson, C (2006)
We report the secreted expression by Pichia pastoris of two human lysozyme variants F57I and W64R, associated with systemic amyloid disease, and describe their characterization by biophysical methods. Both variants have a substantially decreased thermostability compared with wild-type human lysozyme, a finding that suggests an explanation for their increased propensity to form fibrillar aggregates and generate disease. The secreted yields of the F57I and W64R variants from P. pastoris are 200- and 30-fold lower, respectively, than that of wild-type human lysozyme. More comprehensive analysis of the secretion levels of 10 lysozyme variants shows that the low yields of these secreted proteins, under controlled conditions, can be directly correlated with a reduction in the thermostability of their native states. Analysis of mRNA levels in this selection of variants suggests that the lower levels of secretion are due to post-transcriptional processes, and that the reduction in secreted protein is a result of degradation of partially folded or misfolded protein via the yeast quality control system. Importantly, our results show that the human disease-associated mutations do not have levels of expression that are out of line with destabilizing mutations at other sites. These findings indicate that a complex interplay between reduced native-state stability, lower secretion levels, and protein aggregation propensity influences the types of mutation that give rise to familial forms of amyloid disease.